RAMPing up knowledge of the translocon - Dimitrios Vismpas; Friedrich Förster (eLife, 2024)
Advanced cryo-EM approaches reveal surprising insights into the molecular structure that allows nascent proteins to be inserted into the membrane of the endoplasmic reticulum.